The current and future role of general practitioners in skin cancer care: an assessment of 268 general practitioners3. (June 2014) - van Rijsingen, M.C.J.; van Bon, B.; van der Wilt, G.J.; Lagro‐Janssen, A.L.M.; Gerritsen, M.J.P.
Summary Background Given the increase in skin cancer (SC) it seems inevitable that general practitioners (GPs) will play a larger role in SC care in the near future. Objectives To obtain insights into the opinion of GPs with respect to their role in SC care, and their SC knowledge and skills. Methods A self‐administered questionnaire was sent to GPs in the region of Nijmegen, the Netherlands. Results In total 268 GPs (49%) responded. An overwhelming majority were willing to extend their role in SC care. Furthermore, we noted the following results: (i) > 50% of GPs requested additional SC knowledge; (ii) GPs often treat actinic keratosis (AK) themselves, primarily with cryotherapy; (iii) > 50% would treat (low‐risk) basal cell carcinoma (BCC) after additional training; (iv) only a few GPs are familiar with BCC guidelines; (v) the majority of patients with high‐risk SC are referred to dermatologists; (vi) only a few GPs perform total body inspection and palpation of lymph nodes; and (vii) a large number of GPs inform their patients on risk factors in SC development. Conclusions Most GPs are willing to extend their role in SC care; however, more training is requested and the usage of guidelines should be encouraged. Those willing to extend their role should focus on improving their clinical diagnosis of skin tumours, treatment of low‐risk skin (pre)malignancies, including field‐directed treatment of AK and noninvasive treatment of BCC, and on prevention.